How do interconnected dynamics of climate, security and human mobility interplay in Mali: Climate security pathway analysis - Synnestvedt, Thea; Penel, Charlotte; Sarzana, Carolina; Cisse, Sokhna Ramatoulaye; Madurga Lopez, Ignacio (2025)
In Mali, severe droughts and floods are becoming increasingly prominent, with average temperatures increasing. The climatic changes are leading to loss of livelihoods which exacerbate already poor socio-economic conditions. Simultaneously, tensions have been ongoing since Mali’s independence from colonialist powers in the 1960’s reaching new heights in 2012 with the Tuareg rebellion, which escalated into armed conflict. This has reduced the resilience and adaptive capacities of individuals, communities, and the state to respond to climate-related risks, while climate change and extreme weather events have exacerbated vulnerabilities, heightening conflict risks. Human mobility is a common form of adaptation to climate change, as well as violence and armed conflict. The impact of climate change on natural resources and livelihoods compels people to migrate or engage in transhumance livelihoods to sustain themselves, while more immediate climatic hazards such as natural disasters cause immediate displacements, impacting the overall human security situation. Similarly, conflict, especially in the Sahel region, has triggered widespread displacement.